Safety and Effectiveness of BPaL-Based Regimens to Treat Multidrug-Resistant TB: First Experience of an Italian Tuberculosis Referral Hospital - Gina Gualano; Maria Musso; Paola Mencarini; Silvia Mosti; Carlotta Cerva; Pietro Vittozzi; Antonio Mazzarelli; Angela Cannas; Assunta Navarra; Stefania Ianniello; Paolo Faccendini; Fabrizio Palmieri (Antibiotics)
Background/Objectives: Tuberculosis (TB) is preventable and curable, but multidrug-resistant TB (MDR-TB) and extensively drug-resistant TB (XDR-TB) pose significant challenges worldwide due to the limited treatment options, lengths of therapies, and high rates of treatment failure. The management of MDR-TB has been revolutionized by all oral anti-TB drug regimens that are likely to improve adherence and treatment outcomes. These regimes include bedaquiline (B), pretomanid (P), and linezolid (L) (BPaL), and moxifloxacin if resistance to fluoroquinolones is not detected (BPaLM). Based on the evidence generated by the TB-PRACTECAL and ZeNix randomized controlled trials, BPaL/BPaLM regimens are recommended over the currently recommended longer regimens in patients with MDR-TB or monoresistance to rifampin (RR). To our knowledge, no data are currently available on the implementation of BPaL/BPaLM regimens in Italy. Results: Seventeen patients completed the BPaL/BPaLM regimen, with a treatment success rate of 90% (17/19), consistent with the literature data. Eleven patients out of the nineteen retained in care (58%) complained about symptoms consistent with adverse events (AEs). No treatment interruption was necessary due to AEs. Methods: Here, we report the real-world experience of a tertiary referral hospital for TB in Italy, from 2022 to 2024, in the management, outcomes, and adverse drug reactions of a cohort of twenty-two MDR/RR patients treated with BPaL and BPaLM regimens. Conclusions: BPaL-containing regimens also serve as promising options for patients with RR/MDR-TB in terms of real-life experience, but further multicentric studies are required in Europe to confirm the efficacy of shorter regimens to eliminate MDR TB.